Marital Satisfaction amongst Parents of Children with Attention Deficit Hyperactivity Disorder and Normal Children - Reza Rostami; Farideh Farokhzadi; Ahmad Alipour; Mohammad Reza Mohammadi; Mehdi Dehestani; Maryam Salmanian (Iranian Journal of Psychiatry, 2012)
Objective: The aim of this study was to compare marital satisfactionbetween parents of children with attention deficit hyper activity disorder (ADHD) and parents of normal children.Methods: In this study we have selected 400 parents (200 parents of children with ADHD and 200 parents of normal children), whose children age range was 6-18 years. Data were collected using Enrich marital satisfaction Questionnaire, Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime Version (K-SADS-PL) and Conner’s Questionnaire (parent and self-report forms). For data analysis, SPSS software17, bivariate χ2- test, and independent t- test were used.Results: The mean of marital satisfaction in parents of normal children was higher than parents of ADHD children. In the bivariate χ2- test, the p value was less than 0.05, and the obtained t was more than the table-t (1.96), so it can be assumed that there is a significant difference between parents of normal children and those with ADHD children in their marital satisfaction. The level of marital satisfaction (strongly agree level) was 2.8% lower among parents of ADHD children compared to parents of normal children.Conclusions: Findings indicate that parents with ADHD children have lower level of marital satisfaction than parents with normal children.